The training response of highly trained swimmers
The training responses of world-class and national qualifier swimmers were compared. The major emphasis of the study was to look at overtraining and maladaptation states. Implications: Three major coaching principles were developed. 1. Poor performances are likely to be caused as much by poor programming (maladaptation) as overtraining. Individualized training programs of a specific nature are essential for improving swimmers' performances. 2. Blood chemistry markers need to be monitored for at least two weeks before they can be used to verify an overtrained state. By that time other indices, such as behavior, performance, and motivation will have indicated the overtrained state. A single elevated blood marker does not mean that overtraining exists. 3. The greatest risk of maladaptation occurs in the early phases of training when volumes and intensities may be too high and recovery insufficient. Adequate recovery between demanding workloads and training stimuli will reduce the impact of maladaptation.